Discovery of in vivo Virulence Genes of Obligatory Intracellular Bacteria by Random Mutagenesis - Bekebrede, Hannah; Lin, Mingqun; Teymournejad, Omid; Rikihisa, Yasuko (Frontiers in Cellular and Infection Microbiology, 2020)
Ehrlichia spp. are emerging tick-borne obligatory intracellular bacteria that cause febrile and sometimes fatal diseases with abnormal blood cell counts and signs of hepatitis. Ehrlichia HF strain provides an excellent mouse disease model of fatal human ehrlichiosis. We recently obtained and established stable culture of Ehrlichia HF strain in DH82 canine macrophage cell line, and obtained its whole genome sequence and annotation. To identify genes required for in vivo virulence of Ehrlichia, we constructed random insertional HF strain mutants by using Himar1 transposon-based mutagenesis procedure. Of total 158 insertional mutants isolated via antibiotic selection in macrophage cell line DH82, 74 insertions were in the coding regions of 55 distinct protein-coding genes, including TRP120 and multi-copy genes, such as p28/omp-1, virB2, and virB6. Among 84 insertions mapped within the non-coding regions, seven are located in the putative promoter region since they were within 50 bp upstream of the seven distinct genes. Using limited dilution methods, nine stable clonal mutants that had no apparent defect for multiplication in DH82 cells, were obtained. Mouse virulence of seven mutant clones was similar to that of wild-type HF strain, whereas two mutant clones showed significantly retarded growth in blood, livers, and spleens, and the mice inoculated with them lived longer than mice inoculated with wild-type. The two clones contained mutations in genes encoding a conserved hypothetical protein and a staphylococcal superantigen-like domain protein respectively, and both genes are conserved among Ehrlichia spp., but lack homology to other bacterial genes. Inflammatory cytokine mRNA levels in the liver of mice infected with the two mutants were significantly diminished than those infected with HF strain wild-type, except IL-1β and IL-12 p40 in one clone. Thus, we identified two Ehrlichia virulence genes responsible for in vivo infection, but not for infection and growth in macrophages.